Exploring the Impact of VR Scaffolding on EFL Teaching and Learning: Anxiety Reduction, Perceptions, and Influencing Factors - Hsiang Ling Huang (Multimodal Technologies and Interaction, 2024)
This study examined the use of virtual reality (VR) scaffolding in English as a Foreign Language (EFL) instruction, focusing on its effects on speaking anxiety and learner perceptions and the need for tailored assessment methods. The study involved 34 Taiwanese university medical students and utilized quantitative and qualitative questionnaires. The quantitative results indicated a significant reduction in speaking anxiety and positive perceptions of VR-assisted learning. Qualitative findings revealed that students experienced dual anxieties related to language and technology during VR learning and nervousness during performance evaluations in a VR setting. This study highlights the importance of creating interactive scaffolding that considers individual learner differences and supports personalized learning experiences. It also underscores the necessity of adopting assessment strategies that align with VR environments’ unique, immersive nature in language instruction. Our findings contribute to the growing body of research on VR applications in language learning, offering valuable insights for educators and researchers aiming to leverage this innovative technology in the EFL context.